A Systematic literature review of project-based learning on English Writing Skills - Nurul Farihah Rosli,; Nurul Ajleaa Abdul Rahman,; Goh, Ying Soon (Penerbit Universiti Kebangsaan Malaysia, 2024)
Project-based learning (PjBL) is a student-centred approach focusing on experiential learning. The approach has been widely used in the field of sciences and mathematics but not in social sciences, particularly in English writing skills. As PjBL gains popularity as one of the 21st century teaching and learning approaches, there is a need to identify the trends, key authors, significant countries, and findings related to PjBL in writing. This paper presents a systematic literature review (SLR) conducted on 17 articles from the year 2018 to 2023 from the Scopus database following the PRISMA guideline. The study focused on PjBL and English writing, employing a systematic literature review to analyse trends, countries, authors, and journals. The analysis reveals dynamic trends of PjBL in the writing field. While the publication output fluctuated over the years, Indonesia emerged as a major contributor, signifying a global interest. A diverse distribution of articles across journals and countries underscores the global impact of PjBL, with notable contributions from Malaysia, China, and Russia. This paper synthesises the key themes from the literature review, emphasising the improvement in writing skills through PjBL and its challenges. The findings underscore PjBL's potential in transforming English writing education, emphasising the importance of addressing challenges for effective integration. The study contributes to the literature through a systematic analysis, providing insights into the trends and recommendations in PjBL in English writing research. Further research should delve into refining PjBL methodologies to maximize its innovative potential in English writing instruction.